Job stress: a study among nurse at Putra Specialist Hospital (Melaka) Sdn. Bhd. / Fatin Syuhada Arman Shah and Salwah Mohamed Nor - Arman Shah, Fatin Syuhada; Mohamed Nor, Salwah (Faculty of Business and Management, 2015)
Job stress is a serious employment issue that organization should concern about. Besides, to managing and coping with stress is a major challenge for organization. The continuous stress can give impact to not only physical and psychological among nurses, but also can give an impact towards organization’s productivity as well. This study was conducted to identify the relationship between the job stressor such as role ambiguity, role conflict and work overload towards job stress. The data were collected by using questionnaire at Putra Specialist Hospital (Melaka) Sdn Bhd. The findings show that role ambiguity, role conflict and work overload were significantly and positively correlated with job stress. Therefore, to reduce job stress among nurse at Putra Specialist Hospital (Melaka) Sdn Bhd, organization should provide mentoring program and hiring additional nurse in reducing job stress among nurse.